Analysis of the Personality Diagnostic Test in Children with Severe Allergic Rhinitis - Hara, Akiko; Araki, Yasutomo; Kawano, Kenji; Kikawada, Toru (International Journal of Practical Otolaryngology, 2018)
Pediatric allergic rhinitis is a disease characterized by paroxysmal sneezing, runny nose, and nasal obstruction. In addition, there can be mental/psychological problems, but these aspects have not been precisely clarified. We investigated the psychological characteristics of children with severe pediatric allergic rhinitis. The subjects were 40 children with drug-resistant severe pediatric allergic rhinitis. Personality diagnostic tests were conducted using the TS-type infant/child character diagnostic test method. Compared with normal children, children with severe allergic rhinitis had more emotional instability (i.e., lack of confidence in daily life and strained tension), a greater lack of self-control (i.e., outrageous anger induced by immature control of emotions and a lack of self-suppression), and more dependency (i.e., a lack of independence from parents and surrounding people, and a lack of desirable social development during childhood). Instability at home was also observed. These results suggested that severe allergic rhinitis affected mental and personality traits of children. Therefore, it might be important to take these mental/psychological problems into consideration while considering the medical treatment of these patients.
Keywords: pediatric allergic rhinitis; nasal obstruction; mental aspect